Evaluation of Anti-Depressant Activity of spirulina, a blue-green algae on Chronic Unpredictable Stress Induced Depression in Rats - Basavarajappa, Girish Meravanige; Balaraju, Juturu; Naveen, Nimbagal Raghavendra; Goudanavar, Prakash; Ganesh, Vakkalagadda Siva; Nagaraja, Sreeharsha; Shiroorkar, Predeepkumar Narayanappa; Telsang, Mallikarjun (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Depression is a crippling and pervasive illness that can affect a person in many different ways. It can be identified by certain symptoms, such as modifications in behaviour, psychological functioning, and brain physiology. Materials and Methods: One of the animal models for depression has been the Chronic Unpredictable Mild Stress (CUMS) paradigm. In this study, spirulina algae, which contains tryptophan, was chosen and tested for its anti-depressant effectiveness in the CUS model using Fluoxetine as the gold standard. Wistar rats were chosen to undergo the CUS process for 28 days, and throughout that time, the test drug was given at doses of 400 mg/kg. Results: Behavioural and biochemical parameters were analysed, and has shown significant changes. Conclusion: When compared to the CUS group, spirulina algae at the tested doses had a substantial impact on behavioural and metabolic testing. These findings demonstrated that Spirulina algae specifically exhibited an in vivo anti-depressant-like effect.
Keywords: Antidepressant; Spirulina algae; Force swim test; Tail suspensstion test; Sucrose preference test; Chronic Unpredictable Stress